MPP6 stimulates both RRP6 and DIS3 to degrade a specified subset of MTR4-sensitive substrates in the human nucleus. Issue 15 (29th July 2022) - Fujiwara, Naoko; Shigemoto, Maki; Hirayama, Mizuki; Fujita, Ken-ichi; Seno, Shigeto; Matsuda, Hideo; Nagahama, Masami; Masuda, Seiji
Abstract: Recent in vitro reconstitution analyses have proven that the physical interaction between the exosome core and MTR4 helicase, which promotes the exosome activity, is maintained by either MPP6 or RRP6. However, knowledge regarding the function of MPP6 with respect to in vivo exosome activity remains scarce. Here, we demonstrate a facilitative function of MPP6 that composes a specific part of MTR4-dependent substrate decay by the human exosome. Using RNA polymerase II-transcribed poly(A) + substrate accumulation as an indicator of a perturbed exosome, we found functional redundancy between RRP6 and MPP6 in the decay of these poly(A) + transcripts. MTR4 binding to the exosome core via MPP6 was essential for MPP6 to exert its redundancy with RRP6. However, at least for the decay of our identified exosome substrates, MTR4 recruitment by MPP6 was not functionally equivalent to recruitment by RRP6. Genome-wide classification of substrates based on their sensitivity to each exosome component revealed that MPP6 deals with a specific range of substrates and highlights the importance of MTR4 for their decay. Considering recent findings of competitive binding to the exosome between auxiliary complexes, our results suggest that the MPP6-incorporated MTR4-exosome complex is one of the multiple alternative complexes rather than the prevailing one. Graphical Abstract: